2012
DOI: 10.1073/pnas.1106023109
|View full text |Cite
|
Sign up to set email alerts
|

Surprising complexity of the Asf1 histone chaperone-Rad53 kinase interaction

Abstract: The histone chaperone Asf1 and the checkpoint kinase Rad53 are found in a complex in budding yeast cells in the absence of genotoxic stress. Our data suggest that this complex involves at least three interaction sites. One site involves the H3-binding surface of Asf11 with an as yet undefined surface of Rad53. A second site is formed by the Rad53-FHA1 domain binding to Asf1-T 270 phosphorylated by casein kinase II. The third site involves the C-terminal 21 amino acids of Rad53 bound to the conserved Asf1 N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 28 publications
(51 reference statements)
2
28
0
Order By: Relevance
“…In yeast, Asf1 and the checkpoint kinase Rad53 are found in a complex in budding yeast cells in the absence of genotoxic stress (Jiao et al, 2012). Upon replication stress caused by hydroxyurea, the Asf1-Rad53 complex dissociates, suggesting that the complex is regulated by genotoxic stress conditions (Jiao et al, 2012). In addition, Asf1 is important for the transcriptional derepression of two DNA damage response genes during the S phase in response to hydroxyurea (Minard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In yeast, Asf1 and the checkpoint kinase Rad53 are found in a complex in budding yeast cells in the absence of genotoxic stress (Jiao et al, 2012). Upon replication stress caused by hydroxyurea, the Asf1-Rad53 complex dissociates, suggesting that the complex is regulated by genotoxic stress conditions (Jiao et al, 2012). In addition, Asf1 is important for the transcriptional derepression of two DNA damage response genes during the S phase in response to hydroxyurea (Minard et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we here demonstrate that major CPD removal mechanisms are unaffected in mutant plants, suggesting that ASF1 activities participate in CPD photorepair in Arabidopsis, because in the RNAi plants, chromatin is more accessible to damage accumulation, and not because ASF1 proteins regulate the expression of repair enzymes. In yeast, Asf1 and the checkpoint kinase Rad53 are found in a complex in budding yeast cells in the absence of genotoxic stress (Jiao et al, 2012). Upon replication stress caused by hydroxyurea, the Asf1-Rad53 complex dissociates, suggesting that the complex is regulated by genotoxic stress conditions (Jiao et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The checkpoint kinase Mec1 and the Ddc1-Mec3-Rad17 sliding clamp regulate the interaction between Asf1 and Rad53 (Hu 2001;Sharp et al 2001;Burgess et al 2014). Since the asf1-V94R mutation also affects Asf1-Rad53 interaction (Jiao et al 2012;Dennehey et al 2013), we tested the viability of the Rad53-A806R-L808R (rad53-ALRR) mutant, which is strongly affected in its interaction with Asf1 (Jiao et al 2012) in the rrm3D background. We found that the rad53-ALRR rrm3D double mutant is viable ( Figure 1C, iii).…”
Section: Loss Of Chaperone Function Of Asf1 Causes Rrm3d Lethalitymentioning
confidence: 99%
“…Asf1 participates in the assembly and disassembly of chromatin through its H3 histone chaperone activity, in transcriptional silencing via an interaction with Hir1 and in several aspects of the cellular response to genotoxic stress through an interaction with H3 or Rad53 (Hu 2001;Sharp et al 2001;Sutton et al 2001;Celic et al 2006;Recht et al 2006;Takahata et al 2009;Jiao et al 2012;Burgess et al 2014).…”
Section: Loss Of Chaperone Function Of Asf1 Causes Rrm3d Lethalitymentioning
confidence: 99%
See 1 more Smart Citation